2005
DOI: 10.1086/426378
|View full text |Cite
|
Sign up to set email alerts
|

A Toy Model for Gamma‐Ray Bursts in Type Ib/c Supernovae

Abstract: A toy model for gamma-ray burst-supernovae (GRB-SN) is discussed by considering the coexistence of baryon poor outflows from black holes (BHs) and a powerful spin-connection to surrounding disk, giving rise to consistent calorimetry as described by van Putten (2001a) in a variant of the Blandford-Znajek process (BZ, 1977). In this model the half-opening angle of the magnetic flux tube on the horizon is determined by the mapping relation between the angular coordinate on the BH horizon and the radial coordinate… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 34 publications
(31 reference statements)
0
32
0
Order By: Relevance
“…It is shown that this system has a precession period of about a second. The Lense-Thirring precession appears for a Kerr BH, if the accretion disk is inclined with respect to the equatorial plane of the BH (Lense & Thirring 1918). Recently, Reynoso et al (2006, hereafter RRS06) studied the possible effect of Lense-Thirring precession on neutrinocooled accretion disks.…”
Section: Precessing Jetmentioning
confidence: 99%
“…It is shown that this system has a precession period of about a second. The Lense-Thirring precession appears for a Kerr BH, if the accretion disk is inclined with respect to the equatorial plane of the BH (Lense & Thirring 1918). Recently, Reynoso et al (2006, hereafter RRS06) studied the possible effect of Lense-Thirring precession on neutrinocooled accretion disks.…”
Section: Precessing Jetmentioning
confidence: 99%
“…With the consideration to the spin-up process due to accretion and the spin-down process due to the BZ process, the BH spin parameter always evolves to an equilibrium value (Lei et al 2005) so that the a • -dependence essentially does not enter the problem. As shown in Figure 2, the m-dependence will add to the scatter in the correlations.…”
mentioning
confidence: 99%
“…The BZ luminosity can be estimated as (e.g., Lei et al 2005;Krolik & Piran 2011;Kawanaka et al 2013b;Liu et al 2015b)…”
Section: Magnetized Bh-ndafsmentioning
confidence: 99%